Establishing a standard fibroblast cell line derived from kidney tissue of Sumatran rhinoceros (puntung) - Jenuit, Mellinda (Kulliyyah of Science, International Islamic University Malaysia, 2020)
Establishment and cryopreservation of cell cultures have been applied in biodiversity conservation, essential to critically endangered wildlife such as the Sumatran rhinoceros. It serves as the foundation for advanced cellular techniques. Obtaining desired tissues from living organism as a source for primary culture is not feasible. As alternative, preserved tissues from Puntung which was euthanized due to terminal skin cancer was utilized. The aim of this study is to establish, characterize and authenticate fibroblast cells derived from kidney tissue of Sumatran rhinoceros carcass. Primary cultures were isolated from kidney tissue using mixed enzymatic-explant method, supplemented with complete media (DMEM + 10% FBS + 1% antibiotic) and kept at 37ºC with 5% CO2 incubator. Following routine trypsinization, viability and growth curves were obtained by Trypan blue counting method. Frozen stocks were preserved in media containing 90% FBS and 10% DMSO. Cellular senescence was quantified by Sa-β-gal staining assay, while chromosome spreads were stained with Giemsa solution. Mycoplasma contaminations were detected by PCR method. Derivation of fibroblast cells from the kidney tissues generates a total of 81 frozen stocks. The cell viability maintained over 80% during serial passages and after 3 months of cryopreservation, but only cells at P5 and P10 show reasonable recovery after 6 months. From the growth curves, the cell population doubling time at P5 was 20.45h while 22.35h at both P10 and P15. The senescence level significantly increase from P5 to P10, and especially significant at P15. Genetic stabilities were considered stable at P5 and P10. All cultures were free from mycoplasma contamination. The results of this study have concluded that cells cultured up to P10 were suitable for the development of Sumatran rhinoceros cell banking system, which are applicable for advanced research. This also provides simple reference in the development of cell bank for other endangered wildlife in Malaysia.